Yoga and the Gut-Brain Axis: A Systematic Review of its Impact on Mental Health and the Gut Microbiome - Kaur, Paramjeet (International Research Journal of Ayurveda & Yoga, 2025)
Background: The gut-brain axis (GBA) represents a complex, bidirectional communication network that connects the emotional and cognitive centers of the central nervous system with peripheral intestinal functions. This intricate system, which includes the enteric nervous system, the vagus nerve, and the hypothalamic-pituitary-adrenal axis, is profoundly influenced by the gut microbiome. Dysregulation of the GBA and a resulting microbial imbalance, or dysbiosis, have been implicated in the pathophysiology of both gastrointestinal disorders and mental health conditions, such as anxiety and depression. Yoga, an ancient mind-body practice, is increasingly being explored as a non-pharmacological therapeutic intervention for stress-related illnesses. Objectives: The objective of this report is to conduct a narrative synthesis of the available evidence to explore the impact of yoga on mental health and the gut microbiome, with a particular focus on the mediating role of the GBA. A secondary objective is to contextualize these modern scientific findings within the framework of classical Ayurvedic principles, which have long posited a fundamental connection between the mind and digestive health. Methods: This review is a structured narrative synthesis based on a curated set of research materials, not a de novo systematic review. The methodology for reporting aligns with the Preferred Reporting Items for Systematic reviews and Meta-Analyses statement to ensure transparency and reproducibility. The analysis draws from a diverse body of literature, including systematic reviews, pilot studies, and classical Ayurvedic texts. Key data points and thematic elements related to GBA physiology, yoga’s effects on mental health, its influence on the gut microbiome, and the ancient Ayurvedic mind-body link were extracted and synthesized to form a cohesive narrative. Results: The synthesized evidence indicates that yoga practice modulates the GBA by influencing several key pathways. Physiologically, it promotes a shift from the sympathetic “fight-or-flight” response to the parasympathetic “rest-and-digest” state, mediated by the vagus nerve. This process is associated with a significant reduction in stress hormones, such as cortisol. Preliminary human studies suggest that yoga and meditation can directly alter the composition of the gut microbiome, leading to an enrichment of beneficial bacterial genera, such as Megamonas and Faecalibacterium, which have been linked to improved mental and physical health. The classical Ayurvedic concepts of Agni (digestive fire) and Manas (mind) provide a compelling conceptual parallel, with ancient texts describing how mental distress can directly disrupt digestion. Conclusion: The evidence presented supports the hypothesis that yoga can serve as a beneficial adjunctive therapy for mental health conditions by positively influencing the gut microbiome and GBA. The striking congruence between modern neuroscientific findings and the ancient Ayurvedic understanding of the mind-body connection underscores the potential for a holistic, integrated paradigm for understanding and promoting wellness.